Do Teachers’ Beliefs in the Rationale for Learning and teaching Arabic Support the Intended Specific Purpose? - Sayeed, Mahmud bin (UIII Press, 2024)
The present study was developed to assess teachers' beliefs on (1) the rationale for learning Arabic in independent Muslim secondary schools in the UK; (2) Arabic language resources used at these schools; (3) the types of Arabic taught in these schools. Four independent Muslim secondary school teachers of Arabic from Greater London, Birmingham, and Walsall participated in this small-scale qualitative study. Through the semi-structured interview schedule, teachers were asked to answer questions about the rationale for learning Arabic, what types of Arabic they teach, and the resources they use to support the intended goals. Thematic analysis was used to examine the data. Overall findings imply that teachers typically hold similar opinions regarding the three subjects under consideration. Since many teachers exhibit attitudes that imply limited awareness of the desired results, the article discusses the necessity of introducing modules on Arabic for special purposes and Arabic language teacher training programmes. The report advises authors and policymakers to provide resources tailored toward Arabic for specific purposes.